ANALISIS OZONASI LIMBAH CAIR BLACK LIQUOR DARI INDUSTRI PULP DAN KERTAS - Nida Sopiah; Fuji Suciati; M Abdul Kholiq; RTM Sutamiharja (Jurnal Ecolab, 2008)
Black liquor is wastewater coming from pulp processing containing organic and inorganic material which are difficultto degrade. Ozone is a potent oxidator which has capacity to break down chemical bond. Ozonation for 180 minuteswith capacity of 178.3 mg 03/hour could alter the properties and characteristic of black liquor from brownish black tobright yellowish. This was confirmed by the change of maximum absorbance from 0.07 to 0.05 at wavelength 731.5 mmand appeared the absorbency on (nm unit): 340.0, 292.5, 285.5, 284.0, 283.0, 281.5, 280.5. The COD content wasdecreased 33% after ozonation.